Efeitos do treinamento resistido e da reposição de 17beta-estradiol em ratas ovariectomizadas na modulação de p-AKT e PARP-1 clivada no hipocampo - Lagoeiro, Cristiani Gomes (2016)
Menopause is a physiological process associated with physiological changes that lead to increased incidence of some diseases such as sarcopenia, cardiovascular disease, diabetes mellitus and neurodegenerative diseases. Apoptotic process is essential for the maintenance and development of tissues. However, exacerbation of this process can lead increase to neuronal death in neurodegenerative diseases. Objective: To investigate the effects of resistance training and 17β-estradiol replacement on the modulation of p-AKT and cleaved PARP-1, proteins envolved in apoptotic process, in the hippocampus of ovariectomized rats. Methods: 66 female rats Holtzman were randomly divided into six groups: 1) Sham operated Sedentary (Sham-Sed); 2) Sham operated Resistance Training (Sham-RT); 3) Ovariectomized Sedentary (Ovx-Sed); 4) Ovariectomized Resistance Training (Ovx-RT); 5) Ovariectomized Sedentary with 17β-estradiol Replacement (Ovx-Sed-ER); 6) Ovariectomized Resistance Training with 17β-estradiol Replacement (Ovx-RT-ER). The RT protocol required the animals to climb a 1.1 m-long vertical ladder with weights attached to their tails. Each session consisted of 4 to 9 climbs with 2 minutes interval between climbing, performed once every three days for 12 weeks. Protein content of p-AKT and cleaved PARP-1 were analyzed by Western Blotting and concentrations of 17β-estradiol were determined by ELISA. Results: Our results indicate that Ovx-RT groups and Ovx-RT-ER had lower protein content of cleaved PARP-1 compared to Ovx-Sed groups and Ovx-Sed-ER respectively and higher protein content of p-AKT compared to the group Ovx-Sed in the hippocampus. Conclusion: The results of this study show that resistance training performed for 12 weeks, with or without ER may be an effective intervention to promote greater protein content of p-AKT associated with the pathway of cell survival and lower protein content PARP-1 cleaved associated with apoptosis pathway.